Participation Design of Fabric Material Utilization - Widyastuti, Putri Anggraeni (Jurnal Strategi Desain dan Inovasi Sosial, 2024)
Fabric is the main material in producing bags in Kadugenep village. The purpose of the research is to involve participatory design in the design of learning products that can improve the creative process of PAUD HI BKB Kemas Kemas students, in order to utilize the potential of fabric material which is a natural resource in Kadugenep Village. Qualitative research was conducted by collecting data from site observations, interviews with related parties, and literature studies related to the utilization of fabrics by PAUD activities through a participatory design approach. Community service activities have been held at PAUD HI BKB Kemas Kutilang in the post-pandemic era in 2022 and new normal in 2023 as a form of utilization of one of the fabric materials. Flannelette and calico fabric were chosen in the activity. The combination of calico fabric on the drawstring fabric and flannel fabric on the floral motif is applied using a textile glue paste technique that is safe for children of early childhood age. The flannel fabric was applied using a weaving technique on the plastic frame of the shell-shaped handheld fan to produce a plane. In conclusion, the design of learning products formed based on the participation of PAUD HI BKB Kemas Kutilang students can finally be applied by utilizing calico and flannel fabric materials that are safe and comfortable.